PROGRAM FORCLIME (FOREST AND CLIMATE CHANGE) DALAM PENANGGULANGAN MASALAH KERUSAKAN HUTAN DAN EMISI KARBON DI WILAYAH KALIMANTAN 2010-2014 - Hilvan Saputra; Yuli Fachri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research using the concept by applying the role conduct of the programs to see how is the effects in tackling deforestation and emission issue in Kalimantan during 2010-2014 in three focus area. This research using the role theory and International Organisation level analysis. These concept pointing to quantitative method dan library research as source of information.Some of contents in FORCLIME program in tackling id of the core issue are strategic approaches, by monitoring Forclime in three scoope area: Kapuas Hulu, Berau and Malinau. So far these efforts gave good contribution of reducing emission in Kalimantan during 2010-2014, and open eyes of citizen to act proactively in Kalimantan for the good future.Keywords: FORCLIME, deforestation, GIZ, emission, program